The Effect of Oxytocin Massage on First-Stage Labor Pain - Wahyu Abadi Junjung Drajad; Kusumaningtyas, Kharisma; Maharrani, Titi; Alfiah, Siti (Universitas Nahdlatul Ulama Surabaya, 2025)
Pain during labor results from uterine contractions that cause cervical dilation, often leading to increased anxiety, vasoconstriction, and decreased oxygen levels. These factors can contribute to prolonged labor for the mother and potential hypoxia for the fetus. Effective pain management techniques, such as oxytocin massage, may help alleviate labor pain and improve maternal comfort. This study aimed to analyze the effect of oxytocin massage on first-stage labor pain. This quantitative study employed a pre-experimental one-group pretest-posttest design. The research was conducted at TPMB Afah Fahmi, Surabaya, involving 17 laboring mothers selected through purposive sampling. Pain levels were measured using the Numeric Rating Scale (NRS) ranging from 0 to 10. Data were analyzed using the Paired Sample T-Test. Statistical analysis showed a significant reduction in first-stage labor pain following oxytocin massage, with a p-value of 0.000 (p < 0.05). This indicates a meaningful difference in pain levels before and after the intervention. Oxytocin massage effectively reduces first- stage labor pain, promoting a more comfortable labor experience. Healthcare providers are encouraged to integrate oxytocin massage as a non-pharmacological pain management strategy to support laboring mothers.